Anthraquinone-modified nitrogen-doped graphene aerogel for boosting energy density of supercapacitors by self-matching of capacity. (10th October 2021) - Yang, Lifang; Zhuo, Kelei; Xu, Xiaochao; Zhang, Zezhong; Du, Quanzhou; Bai, Guangyue; Wang, Jianji
Abstract: When an electrode (negative/positive) with excellent capacity matches a counter electrode with relatively low capacity or a pair of excellent electrodes cannot match each other, overall performance of the constructed supercapacitors (SCs) will be limited. Here, we report a novel electrode material 1, 5-diamino-4, 8-dihydroxyanthraquinone (DHAQ) grafted nitrogen-doped graphene aerogel (DHAQ-NGA) prepared by simple hydrothermal method. Since DHAQ molecule contains –C(=O)− and −NH−/−OH groups, the DHAQ-NGA composite can act as both the negative and positive electrode materials for a supercapacitor in ionic liquid electrolyte to improve capacity by faradaic reactions on these two electrodes. In addition, the intramolecular hydrogen bonding of DHAQ can improve the stability of the material. Therefore, DHAQ-NGA displays an enhanced specific capacity of 410 C g −1 for the positive electrode and 454 C g −1 for the negative electrode material. The assembled device can deliver a high energy density of 117 Wh kg −1 at a power density of 822 W kg −1 . Graphical abstract: Image, graphical abstract